FEATURES THEORETICAL PRINCIPLES EFFECT ON INTELLECTUAL CAPITAL MANAGEMENT PROCESS - Vasylyshyna, N.Ye. (The actual problems of regional economy development, 2016)
The whole history of humanity is evidence that it sought and continues to seek to optimize the efficiency of the phenomenon of business through rationalization of engagement and use of intellectual, psychological and physical potential of each individual or group of individuals to work to achieve the goals set by the determined community of people depending on prevailing in this community needs and motives, which are the driving force behind its development. The development of effective, adapted to modern conditions of management mechanisms of power companies by using an integrated and systematic management of intellectual resources. JEL: M 20